The extent of knowledge of school principals in Zarqa Governorate of the benchmark performance criteria used in the evaluation of education from their point of view in the light of some variables - Al-Mashagbah, Mutaib Odeh (Journal of Educational and Psychological Sciences, 2018)
The study aimed at revealing the extent of knowledge of school managements in Zarqa Governorate in terms of the reference performance used in the educational evaluation from their point of view in the light of some variables. The researcher used the descriptive approach. To achieve the goal of the study. A random sample was chosen from) 168 (managers and managers. Estimate (high) , an arithmetic mean (3. 67 out of 5) , with regard to the dimensions of the study, which is the following order criteria for the evaluation of the school, with an average (3. 86).) , then the standards related to the ministry at an average of administration (3. 68) , then the standards related to the ministry at an average of (3. 48). All of them were rated (high). The results also showed that there is no statistically significant difference at the level of: the significance between the extents to which managers know the benchmark performance criteria used in educational evaluation due to the variable years of experience and Gender. In the light of the results, a number of recommendations and proposals were presented to raise the level of managers’ knowledge of the benchmark performance criteria in the educational evaluation